Original Error Analysis of the Second Reduction Part of RV Reducer - Zheng Yuxin; Xi Ying; Li Mengru; Hua Binbin; Liu Xianhui (Jixie chuandong)
RV reducer is used in robot as a high precision speed reducer and its allowable transmission rotation angle error is less than 1’,so,in the process of manufacturing and assembling,there are many factors which influence the transmission accuracy of RV reducer seriously. The cycloid gear,crankshaft,output mechanism are important transmission components in the second reduction part,their original errors result in the inaccuracy of the whole machine. Through establishing a transmission four bar mechanism model,the relationship between the three components is expressed,and the direct relationship between input angle and output angle of the second reduction part is established. Through analyzing the four bar model,the effect rules of error on the transmission accuracy is got,the design standard of deviation is established and then error control method is explored,the whole work can play a guiding role in manufacturing and assembling process.